The Relationship of Nurse Stigma During The COVID-19 Pandemic to Nurse Performance at Hospital in Kupang - Gonsalves, Dominggos; Onggang, Fransiskus Salesius; Leo, Mario Stefanus (Green Publisher Indonesia, 2023)
During the COVID-19 pandemic, these professions that are at high risk of contracting COVID-19 can trigger ongoing fear, anxiety, stress, fatigue, and emotional trauma that is exacerbated by the stigma of being a carrier of the disease. This can have an impact on nursing services that are not optimal and decrease in performance. The purpose of this study was to determine the relationship of nurses' stigma during the COVID-19 pandemic to the performance of nurses working at Bhayangkara Drs Hospital. Titus Uly and S. K. Lerik Regional General Hospital, Kupang City. This study was designed using a quantitative study with a Cross Sectional design with Chi Square statistical test. A sample of 67 people was taken using Simple Random Sampling. From the results of the study, it was found that most nurses (98.5%) had a negative stigma during the COVID-19 pandemic and had good performance as much as 81.5%. There is a significant relationship (p value = 0.038) between nurse stigma during the COVID-19 pandemic and nurse performance. This research can be input for hospital leadership regarding attention to nurses and making policies to improve performance that is free of stigma and for nurses themselves to continue to have strong self-coping so as not to cause anxiety and not reduce performance in nursing services/providing care.